2020
DOI: 10.2528/pierm20072303
|View full text |Cite
|
Sign up to set email alerts
|

Applying Electromagnetic Field Analysis to Minimize the Earth Resistance on High Resistivity Soils

Abstract: Different optimization strategies to reduce the earth resistance in a high resistivity soil are discussed in this work and illustrated with a practical example. Finite Element simulations reproducing real-world conditions in terms of structure design and soil profiles have been made to evaluate the improvements that should be adopted to minimize earth resistance. We analyze an example of an earthing system of an array of four identical telescopes installed on high resistivity (kΩ• m order) soils with two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…According to Olowofela et al (2020), soil resistivity greatly influenced the performance of earthing systems. It had been observed that soils with high resistance are not considered appropriate for operative earthing system, as they will compromise the proper function of the earthing system (Ronda et al, 2020). The European standards EN-62305-3 recommend earth resistance of 10 Ω for structures in which direct equipotential bonding is applied (International Electrotecnical Commission [IEC], 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to Olowofela et al (2020), soil resistivity greatly influenced the performance of earthing systems. It had been observed that soils with high resistance are not considered appropriate for operative earthing system, as they will compromise the proper function of the earthing system (Ronda et al, 2020). The European standards EN-62305-3 recommend earth resistance of 10 Ω for structures in which direct equipotential bonding is applied (International Electrotecnical Commission [IEC], 2010).…”
Section: Introductionmentioning
confidence: 99%